Social and behaviour change communication to improve child feeding practices in Ethiopia - Abdulhalik Workicho; Sibhatu Biadgilign; Meghan Kershaw; Rahel Gizaw; Jennifer Stickland; Wossen Assefa; Cherinet Abuye; Behailu Woldegiorgis; Lioul Berhanu; Eileen Kennedy (Wiley, 2021)
Abstract Social and behaviour change communication (SBCC) interventions can positively affect optimal nutritional practices. This study evaluated the added value of a virtual facilitator tool to an enhanced community conversation (ECC) programme to improve infant and young child feeding (IYCF) practice among children under the Growth through Nutrition Activity programme in Ethiopia. The study used a quasi‐experimental design with a control group. Pregnant and/or lactating women were the study population for both study groups. The intervention (ECC + VF) group received all the same components as the control group but had the addition of in‐person ECC meetings supplemented with audio‐recorded virtual facilitators (VF) sessions designed to complement the monthly meeting lesson or topic. A difference in difference analysis was employed using generalized linear mixed model (GLMM) in Stata version 15.0 (Stata Corporation, College Station, TX). A p‐value of less than or equal to 0.05 was considered significant for all tests. Accordingly, a 13.6% change in iron folic acid (IFA) intake for 3 months and above was observed in the intervention group. Even though not statistically significant, large to moderate positive changes in child minimum diet diversity (20%), minimum acceptable diet (18%) and women diet diversity (7.9%) were observed in the intervention group. This study identified the use of virtual facilitators as a modality to transmit standard nutrition messages during ECC programmes for optimal IYCF practices. The findings strengthen the notion that using a combination of SBCC approaches has advantage over a single method in improving important nutritional practices.